2020
DOI: 10.3345/cep.2019.00969
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of conservative treatment of perianal abscesses in children and predictors for therapeutic failure

Abstract: Background: The optimal management of perianal abscess in children is controversial.Purpose: To evaluate the efficiency of conservative treatment of perianal abscess in children and identify parameters that predict therapy failure.Methods: All cases of children younger than 14 years of age with perianal abscesses between 2001–2016 were evaluated.Results: Of the 113 enrolled patients, 64 underwent subsequent surgery for advanced disease (primary surgery group). Conservative treatment was initiated in 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 17 publications
2
16
0
2
Order By: Relevance
“…The rate of fistula (between the PA and the anal crypt) identified at the time of primary drainage varies widely in different studies. The percentage of communication between the PA and the internal (anal) opening was <20% (1,4,6,7,11) or more than 60% (25,27,(29)(30)(31)(32). Our results (approximately 80%) support the latter.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The rate of fistula (between the PA and the anal crypt) identified at the time of primary drainage varies widely in different studies. The percentage of communication between the PA and the internal (anal) opening was <20% (1,4,6,7,11) or more than 60% (25,27,(29)(30)(31)(32). Our results (approximately 80%) support the latter.…”
Section: Discussionsupporting
confidence: 72%
“…The management of PA in infants and children is controversial. It has traditionally been treated surgically by incision and drainage (ID) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). However, in the past two decades, some studies have shown that the conservative management appears to be effective in selected cases (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that local hygiene and systemic antibiotics without surgical drainage minimized fistula formation. Boenicke et al 8) described the efficiency of conservative treatment of perianal abscesses in children and predictors of therapy failure. However, there is some confusion regarding the definition of conservative treatment for perianal abscess.…”
mentioning
confidence: 99%
“…In this article, the authors defined incision and drainage of the perianal abscess as surgical treatment and local care including hygiene, sitz bath, and antibiotics as conservative treatment. 8) However, other articles defined incision and drainage with local care of the perianal abscess as conservative treatment. 2) There are different opinions regarding use of antibiotics in the treatment of perianal abscess and fistula-in-ano in literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation